Investigating the Factors Which Determine the Adoption of Mobile Banking Apps by Youth: The Case of Kuwait and Serbia - Faidon Theofanidis; Massouma Rahat (Proceedings, 2023)
The research objective of the study is to assess the impact of perceived ease of use, perceived usefulness, personal innovativeness, perceived risk, and social influence on the intention to use mobile banking applications by university students in Kuwait and Serbia. Preliminary (Kuwait sample size = 51, Serbia sample size = 31) descriptive statistics and comparisons of means between Kuwait and Serbia confirmed that Kuwaitis perceive mobile banking as related to higher risk compared to Serbians, explaining why Serbians have a more positive attitude towards mobile banking and higher intention to use it.